The isolation and characterization of gram negative bacteria from green sea turtles (Chelonia Mydas) at ornamental fish center, Port Dickson, Negeri Sembilan / Nur Syuhada Yusoff - Yusoff, Nur Syuhada (2018)
The improper handling of green sea turtles in captivity may cause an illness or a disease, such as Salmonellosis to the turtle caretakers or to the people that have a physical contact with the turtles. This may happen due to the attachment or infection of microorganism from the turtles. Therefore, this study was conducted to isolate and characterize the bacteria from green sea turtles (Chelonia mydas) at Ornamental Fish Centre, Port dickson, Negeri Sembilan. The bacteria was isolated and characterized from four different parts of the turtle’s body, which are from the shell, saliva, feces and water tanks of three green sea turtles of the same age and gender. Through the use of selective media and biochemical testing, there were a few bacteria isolated and characterized. The results from this study showed the presence of several Gram negative bacteria from the samples of the green sea turtles such as Escherichia coli, Salmonella and Shigella. It is recommended for the turtle caretakers to take a precaution action when handling the turtles and always concern with the hygienic conditions of the turtle tanks to reduce or avoid the risk of any bacterial infection.